Pemberdayaan Masyarakat Desa Tegal Bogor melalui Pemanfaatan Digital Marketing untuk Mencari Peluang Bisnis - Nurmutia, Syahreen; Hendra, Franka; Ardi P, Gilang (Jurnal PKM Manajemen Bisnis, 2024)
The Community Service Program titled "Strategy for Identifying Business Opportunities through the Utilization of Digital Marketing in Tegal Village, Bogor" was initiated due to the urgent need for MSMEs to adapt to digital technological advancements to enhance their business competitiveness. The goal of this activity was to equip participants with knowledge and skills in digital marketing, which could be used to identify and develop business opportunities. The method employed involved interactive counseling and training sessions covering the use of social media, search engine optimization (SEO), and content marketing. The results of the activity showed a significant increase in participants' understanding and application of digital marketing, with many reporting improved customer interaction and sales. Post-activity survey results also confirmed the program's success, although there remains a need for further training to support more effective and sustainable implementation in the future.